ANALISIS PEMBELAJARAN BIOLOGI DI ERA PANDEMI COVID-19 - Siska Dewi; Novi Fitriandika Sari (Universitas Islam Negeri Sumatera Utara, 2022)
At the beginning of 2020 the learning process in Indonesia was disrupted due to the outbreak of Covid-19. The Indonesian Ministry of Education and Culture has replaced face-to-face learning and learning activities into online-based learning and learning activities. This study aims to analyze online biology learning in the era of the Covid-19 pandemic at SMAN 1 Bilah Hilir. This research used quantitative research with descriptive method. The population in this study were students of class XI (XI IPA-1, XI IPA-2, XI IPA-3, XI IPA-4) at SMA Negeri 1 Bilah Hilir as many as 110 students, while the sampling was carried out by total sampling. with a total of 110 students. Data collection was done by using a questionnaire via Google Form which was distributed online via Whatsapp Group to students containing 25 statements. The results of the study consist of the types of applications used in online learning, the results were, students tend to like the use of the WhatsApp application by 72%, followed by the Google Classroom application by 20%, followed by the Zoom Meeting application by 8% and Google Meet by 0% while the acquisition of online biology learning at SMAN 1 Bilah Hilir, the results were online learning facilities by 72%, student responses by 71%, online learning obstacles by 69%, conformity to schedules by 68%, communication between teachers and students by 68%, enthusiasm and enthusiasm by 67% and understanding of the material by 63%.